Teaching styles: building bridges to approach individual differences of students - González-Peiteado, Margarita; Pino-Juste, Margarita (Revista Complutense de Educación, 2015)
We are aware that in education, if we want to progress towards an effective attention to diversity, it is unavoidable to develop teaching methods that take into account pupils’ individual differences, linked to their interests, necessities, aptitudes, potentialities and particular learning styles. All these features make them unique and differentiated. From the study of inter-personal variability and based on a multidimensional theoretical framework, we describe and analyse interindividual and inter-group differences of 555 students from the Faculties of Education Sciences of Galicia, belonging to the Universities of La Coruña, Santiago de Compostela and Vigo, under the focus of the following different teaching styles: reflexive, cooperative, individualizer, innovative, researcher and academic. The results obtained reveal the existence of significant differences in the preferences on teaching styles according to the four variables posed: University, specialty, sex and age.
Keywords: teaching styles; individual differences; education; initial training; teacher